On Application of Digital Monetary Instruments as a Priority Vector of Innovative Economy Development in the Aspect of the Country’s Economic Security - Svetlana A. Starykh; Olga I. SOLODUKHINA; Daniel I. RASPOPIN; Sergey K. SOLOVYEV (Communications of International Proceedings, 2020)
In modern realities the development of economy and socio-economic, information and technical systems depends on full-scale formation of digital environment and infrastructure (industry). The structured model of digital economy positively influences both the activity of economic entities and the mechanism of functioning of its constituent elements: it allows attracting instruments of investment from outside, to develop and modernize electronic commerce and platforms, taking into account application of new software and digital products. The article analyzes the comparison of the essence of crypt currency and digital money. The classification of digital money and payment systems is considered. The correlation of the terms and e-money, their similarity and difference, as well as their main features are studied, problem aspects and perspective directions of development are revealed.
Keywords: Digital Money; Virtual Currency; Crypt Currency; Bitcoin; Blockchain; Payment System.